Thursday
March 30, 2017

Post a New Question

Posted by on .

solve it:
a) 3 log x with base 8 + 2 = 0
b)2 log (x-1)with base 6 =log 4 with base 6

  • Maths(logarithmic functions) - ,

    a)
    3 log8 x = -2
    log8 x = -2/3
    8^(-2/3) = x
    x = 1/4

    b) 2 log6 (x-1) = log6 4
    log6 (x-1)^2 = log6 4

    (x-1)^2 = 4
    x-1 = ±2
    x = 3 or x = -1 , but for log(x-1) to be defined, x>1

    so x = 3

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question